2022
DOI: 10.14710/jpki.17.1.56-63
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Assistance for Pregnant Women on Attitudes and Behavior Changes in Stunting Prevention

Abstract: Background: East Kotawaringin and Pulang Pisau Regency have highest prevalence of stunting, respectively, in Central Kalimantan Province. One of the efforts made through the assistance to improve the knowledge and skills of pregnant women. The study was aimed at analyzing the effectiveness of assistance on behavior and attitudes among pregnant women in the Pulang Pisau Regency. It also aimed to analyze the behavior of pregnant women shifting upon stunting.Method: It is a quasi-experimental study (n:60), with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
(13 reference statements)
0
4
0
Order By: Relevance
“…Based on the results of the t-dependent statistical test, there was a significant difference before and after giving cookies with red beans p<0.05. ------------------------------------------------------------ -------------------------------------------------------------------------------------------------------------- In the control group, it was shown that from 26 samples for the control group, there was an increase in the average body height from 77.6-77.9 cm, while for albumin levels, there was an increase in the average albumin from 3.18-3.57 g dLG 1 . Based on the results of the t-dependent statistical test, there was a significant difference before and after giving cookies with red beans p<0.05 on the albumin variable indicator, while on the height indicator and Z-Score there was no significant difference p>0.05.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Based on the results of the t-dependent statistical test, there was a significant difference before and after giving cookies with red beans p<0.05. ------------------------------------------------------------ -------------------------------------------------------------------------------------------------------------- In the control group, it was shown that from 26 samples for the control group, there was an increase in the average body height from 77.6-77.9 cm, while for albumin levels, there was an increase in the average albumin from 3.18-3.57 g dLG 1 . Based on the results of the t-dependent statistical test, there was a significant difference before and after giving cookies with red beans p<0.05 on the albumin variable indicator, while on the height indicator and Z-Score there was no significant difference p>0.05.…”
Section: Resultsmentioning
confidence: 96%
“…Table 4, shows that from 26 samples for the treatment group, there was an increase in the average body height from 80.05-81.30 cm, while for albumin levels, there was an increase in the average albumin level from 4.09-4.64 g dLG 1 . Based on the results of the t-dependent statistical test, there was a significant difference before and after giving cookies with red beans p<0.05.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…(Ega. FM, Maryatun, 2020), (Oktaviani & Sulistyawati, 2022). Research in NTT showed that stunting management focused on the period of conception and after, such as supplementary feeding programs and improvement of Posyandu services for toddlers, had not been able to reduce stunting prevalence (Jap J, Sumarmi S, 2019).…”
Section: Discussionmentioning
confidence: 99%